Pengaruh Lingkungan Kerja Dan Kompensasi Terhadap Kepuasan Kerja Karyawan Pada PT Bank Mega Muara Teweh - Azizah, Aulia (JURNAL ILMU EKONOMI (MANAJEMEN PERUSAHAAN) DAN BISNIS, 2020)
This study aims to determine the effect of the work environment on employee job satisfaction at PT. MEGA Bank, Muara Teweh Branch. To determine the effect of compensation on employee job satisfaction at PT. MEGA Bank, Muara Teweh Branch. To determine the effect of the work environment and compensation together on employee job satisfaction at PT. MEGA Bank, Muara Teweh Branch. This research method uses quantitative data types with Multiple Linear Regression analysis tools. The results of data collection have obtained The results of research conducted by researchers prove that the work environment and compensation together (simultaneously) and individually (partially) affect the job satisfaction of employees at PT. MEGA Muara Teweh Bank The research results concluded that the work environment variables have a significant influence on employee job satisfaction. The compensation variable has a significant effect on employee job satisfaction. Work environment and compensation variables simultaneously have a significant effect on employee job satisfaction at PT. MEGA Bank Muara Teweh. To Increase Employee Job Satisfaction at PT. MEGA Muara Teweh Branch through work environment variables in an effort to Increase Employee Satisfaction at PT. MEGA Muara Teweh Branch through compensation variable.